Financial Socialization, Perceptions of Financial Technology, and Entrepreneurial Intention among Generation Z Students: Mediating Role of Financial Inclusion - Sesri Sellina; Abdul Latif; Akfika Rizky Sabilla; Erna Apriani; Lyra Aprilia Putri (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effects of financial socialization and perceptions of financial technology on entrepreneurial intention among Generation Z university students. It also investigates whether financial inclusion mediates these relationships.Method: This study employed predictive quantitative approach using questionnaire survey and purposive sampling. The final sample comprised 200 Generation Z university students in Bekasi Regency. Data was analyzed using partial least squares structural equation modeling (PLS-SEM).Result: This research found that financial socialization has a significant direct effect on entrepreneurial intention. Financial socialization and perceptions of financial technology also significantly affect financial inclusion. However, perceptions of financial technology and financial inclusion do not significantly affect entrepreneurial intention. Furthermore, financial inclusion does not mediate the relationships between financial socialization, perceptions of financial technology, and entrepreneurial intention.Practical Implications for Economic Growth and Development: This study highlights the importance of strengthening financial socialization to foster entrepreneurial intention among Generation Z. Universities, local governments, and financial institutions should provide practical financial education programs that support entrepreneurial decision-making and expand access to financial services.Originality/Value: This study tests financial inclusion as a mediator between financial socialization, perceptions of financial technology, and entrepreneurial intention among Generation Z university students.